Study of high temperature conditions in Misantla bakery - Pérez-Méndez, Ana Roselyn; García-Cruz, Romeo (Renewable Energy, Biomass & Sustainability, 2019)
This document aims to publicize the temperature evaluation carried out in the production area of ​​a bakery in the city of Misantla, said evaluation was carried out to know the temperatures to which the workers in this space are exposed during their working hours, as well as, to determine if the temperatures are within the permissible limits as established in NOM-015-STP-200. The methodology comprised recognition, evaluation, and control of elevated temperature conditions within the bakery. This study is descriptive and is developed as a quantitative investigation. The research population is made up of exposed workers in the bakery. The temperature evaluation was carried out according to the procedure established in point No. 9 of the standard, taking the temperatures with the help of a prototype measuring temperature and relative humidity (prepared at the Higher Technological Institute of Misantla) and a anemometer, obtaining a temperature index of 40.7 ° C, and given this result it has been concluded that the temperature index exceeds the Maximum Permissible Limits of exposure to high temperatures established by the standard, which becomes a threat for the health of Occupationally Exposed Personnel (POE).